FACTORS INFLUENCING FIXED INCOME MUTUAL FUND PERFORMANCE - Triasesiarta Nur; Frederick Valerio Fernandika (Journal of Applied Finance & Accounting, 2022)
A mutual fund is one of the investment instruments currently developing in Indonesia. There are many types of mutual funds, such as money market funds, fixed-income funds, equity funds, and mixed funds. When an investor invests their money in mutual funds, the investor has to be able to pick the best mutual funds based on mutual funds' performance and their risk profile. There are a lot of factors to determine mutual funds' performance. This research aims to analyze the effect of fund age, fund size, expenditure ratio, and past performance on fixed income mutual funds performance starting from 2016 – 2019. The performance of fixed income mutual funds is measured with the Sharpe method. Multiple regression results analyzed data from the research. The research results show that fund age has a negative and significant effect on fixed income mutual funds. Meanwhile, fund size, expenditure ratio, and past performance don’t significantly affect the performance of fixed-income mutual funds. This research provides investors insight into being more selective in choosing mutual fund products, especially fixed income mutual funds. Furthermore, portfolio managers might use this study to assess the performance of the mutual funds they manage. So that the mutual funds they manage might have a higher future performance. The study contributes to a better understanding of the factors to consider when investing in fixed income mutual funds.